(untitled) (Journal of School Administration Research and Development, 2023)
The world currently has more than three billion smartphone users. The smartphone is fully integrated into the daily life of individuals, including 95% of American teenagers. Excessive use of the smartphone leads to smartphone addiction and problematic smartphone use (PSU) which has been associated with depression, stress, reduced self-esteem, and decreased academic performance. This PSU study surveyed high school students grades nine thru twelve from a comprehensive and demographically diverse high school in the United States. This study was conducted with 319 high school students to assess for associations among PSU, depression, stress, self-esteem, grit, and academic performance. Results of this study indicated that students use the smartphone to support learning both inside and outside of the classroom. Results also indicated significant correlations among PSU, depression, stress, self-esteem, grit, and academic performance. Multiple regression analysis found stress, self-esteem, and grit to be significant predictors of PSU. Implications of this study included informing families, educators, district administrators, and policymakers to more fully and rigorously utilize the electronic device policy provided in California Assembly Bill 272 and to implement more robust and thoughtful classroom smartphone policies and practices. Recommendations are to continue to assess and build awareness of PSU among adolescents, especially post COVID-19 pandemic, when interpersonal relationships and personal connections are a focus of social emotional pandemic recovery.